MANAJEMEN CAIRAN PADA PASIEN GAGAL JANTUNG : STUDI KASUS - Subantara, Dandi Oka (Lembaga Penelitian Sekolah Tinggi Ilmu Kesehatan Kuningan, 2023)
Introduction : Heart failure is also associated with aging, there are also significant racial, ethnic and gender differences. Heart failure can also be a clinical syndrome involving impaired heart function, skeletal muscle, kidney function, and neurohumoral dysfunction. Methods: This study uses a nursing process approach. This case study was conducted to determine fluid management in patients with heart failure. Discussion: In this discussion, we will explain how these signs and symptoms are found in heart failure patients and how to manage their fluids. Conclusion: The patient has typical signs and symptoms according to the diagnosis of decreased cardiac output and interferes with one of the basic needs, namely excreting body waste according to the theory of virginia Henderson.